Comprehensive Characterization of Oncogenic Drivers in Asian Lung Adenocarcinoma. Issue 12 (December 2016) - Li, Shiyong; Choi, Yoon‐La; Gong, Zhuolin; Liu, Xiao; Lira, Maruja; Kan, Zhengyan; Oh, Ensel; Wang, Jian; Ting, Jason C.; Ye, Xiangsheng; Reinhart, Christoph; Liu, Xiaoqiao; et al.
ABSTRACT : Introduction: : The incidence rate of lung adenocarcinoma (LUAD), the predominant histological subtype of lung cancer, is elevated in Asians, particularly in female nonsmokers. The mutation patterns in LUAD in Asians might be distinct from those in LUAD in whites. Methods: : We profiled 271 resected LUAD tumors (mainly stage I) to characterize the genomic landscape of LUAD in Asians with a focus on female nonsmokers. Results: : Mutations in EGFR, KRAS, erb‐b2 receptor tyrosine kinase 2 gene ( ERBB2 ), and BRAF ; gene fusions involving anaplastic lymphoma receptor tyrosine kinase gene ( ALK ), ROS1, and ret proto‐oncogene ( RET ); and Met Proto‐Oncogene Tyrosine Kinase ( MET ) exon 14 skipping were the major drivers in LUAD in Asians, exhibiting mutually exclusive and differing prevalence from those reported in studies of LUAD in non‐Asians. In addition, we identified a novel mutational signature of XNX (the mutated base N in the middle flanked by two identical bases at the 5′ and 3′ positions) that was overrepresented in LUAD tumors in nonsmokers and negatively correlated with the overall mutational frequency. Conclusions: : In this cohort, approximately 85% of individuals have known driver mutations ( EGFR 59.4%, KRAS 7.4%, ALK 7.4%, ERBB2 2.6%, ROS1 2.2%, RET 2.2%, MET 1.8%, BRAF 1.1%, and NRAS 0.4%). Seventy percent of smokers and 90% of nonsmokers had defined oncogenic drivers matching the U.S. Food and Drug Administration–approved targeted therapies.